Adaptive Formation for Multiagent Systems Subject to Denial-of-Service Attacks - Pan, Kunpeng; Lyu, Yang; Pan, Quan (IEEE transactions on circuits and systems. I, Regular papers, 2022)
The vulnerabilities of multi-agent-system (MAS) become a critical issue for cybersecurity. The article investigates the formation control problem for MASs under multi-channel denial-of-service (DoS) attacks. In this article, the attacks on each channel are independent, while most of the existing results show that DoS attacks are the same on all channels. Without loss of generality, we consider multi-channel DoS attacks are imposed on a leader-follower MAS. Firstly, we propose a distributed formation control protocol to achieve the desired formation in the presence of DoS attacks. A translation-adaptive method is considered to adjust the interaction weights among neighboring agents online. Furthermore, a performance guarantee is derived based on the state information, and hereafter state errors among all agents can be regulated. Moreover, we derive the sufficient conditions for system stability w.r.t the controller gain and the allowable attack duration in the form of linear matrix inequalities (LMIs). Finally, simulation results are given to illustrate the effectiveness of the proposed method.